(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
In any organization, it’s crucial to have clear office procedures that outline how different departments can work together efficiently. This study proposes the development of office procedures to improve and analyze the gaps in the current system of the Human Resources Department at ABC Construction Company. ABC Construction has provided quality products and services in the manufacturing industry since the 1940s, including fences, building systems, and DIY parts and services. The company has built a strong client-supplier relationship based on trust over four generations. The study employed a qualitative methodology and conducted interviews and surveys with personnel from the Head Department and Human Resources. The survey found that respondents agreed on several problems, including overlapping job descriptions, confidentiality, attendance, and underutilization of email for transactions. The researchers suggest the department use an e-HR website application for proper monitoring. Respondents strongly believed the proposed idea would benefit the Human Resources Department based on the interview. Adapting e-HR would enhance record-keeping avoid loss of information, and misplacement of records. Additionally, employees are capable of using technology in their daily work. While respondents say the company is open to adapting e-HR, it requires thorough preparation and delegation. The proposed process for improvement, including submitting leave forms, resignation letters, and resumes through one email, is feasible. A training session for the termination process can reduce replacements, which adversely affect productivity and progress. A warning agreement can help employees improve their performance and behaviour. The performance evaluation procedure flowchart proposed by the researchers can provide a guideline for evaluating employees. Overall, the respondents strongly agreed that the proposed idea and concept are more likely to be implemented in the Human Resources Department of ABC Construction Company. The study concludes that implementing the proposal will streamline the Human Resources Department’s processes, ensure the fulfilment of relevant duties and responsibilities, and create an effective system for keeping documents essential for the smooth flow of office procedures. The proposed idea could significantly improve the company’s operations, making them more organized and productive.